The Manuscripts of Cædmon’S Hymn and Bede’S Death Song With a Critical Text of the Epistola Cuthberti De Obitu Bedae - Dobbie, Elliott Van Kirk (Columbia University Studies in English and Comparative Literature, 1937)
Presents a scholarly look at the text of Caedmon's hymn and Bede's Death Song.  These two are treated together to demonstrate the homogeneity of their sources and their common association with the name of Bede